HUBUNGAN ANTARA DUKUNGAN SOSIAL AYAH DENGAN PENYESUAIAN SOSIAL PADA REMAJA LAKI-LAKI - Orthorita Putri Maharani; Budi Andayani (Faculty of Psychology, Universitas Gadjah Mada, 2003)
The purpose of this research is to examine the relationship between father`s social support and related male adolescent’s social adjustment. The hypothesis tested was a positive correlation between social support from father and the related male adolescent’s social adjustment. The subjects of this research were 69 male students from three SMUNs in Jogjakarta lived with their fathers. The data was collected using perceived fathers’ social support scale and social adjustment scale. The relationship between fathers’ social support and the adolescents’ social adjustment was tested using product moment analysis, resulting a coefficient correlation of 0.255; (p